The non-refoulement principle in the Malaysian courts: the stumbling block / Dina Imam Supaat - Imam Supaat, Dina (2014)
This study seeks to analyse the applicability of the principle of non- refoulement, an international custom in the Malaysian courts. It begins with the explanation on whether or not there are profound evidence to conclude that the principle has become an international custom and the legal status of international law in the Malaysian legal framework. Analysis then continues on Malaysia‟s position as a dualist state. Another prime focus of this study is the judicial trend relating to international custom as shown in several case laws. Finally it will put forth argument to make the case for the application of the rule in local courts for the benefit of refugees.